Review of Eva Rieger. 2011. Richard Wagner’s Women. Translated by Chris Walton; and Laurence Dreyfus. 2010. Wagner and the Erotic Impulse. - Coleman, Jeremy (Current Musicology, 2013)
The anniversary commemoration of great artistic figures would be incomplete without a survey of the scholarly landscape. So in the year of Richard Wagner’s bicentenary, the publication of new books shows no sign of abating, and nor should it, when there is still so much to be said about this most controversial of composers. But many of the literary products that pass for Wagner scholarship are still beset by popular assumption, blind deference, and trite dismissal, imposing a dead weight that threatens to smother the critical spark that alone can do Wagner justice and demonstrate his startling relevance. It is in this spirit that the present article will individually review two recent publications on gender and sexuality in Wagner, and finally compare them and reflect on wider scholarly trends and possibilities.